Influences of Brand on Hospital Performance and Patient Behavioral Expectations - Yuliani, Yuliani (UI Scholars Hub, 2019)
Increasing number of Hospital in Asia at the present triggers hospital to build a marketing strategy. Hospital branding is one of the choosen way for marketing which giving benefits for internal and externals. This study aims to identify the influences of brand on hospital performance and patient behavioral expectations. The research method is literature review with 7 included studies. Research related to branding in the field of healthcare services was searched using valid keywords, including hospital branding, hospital, patient combined with keywords such as the effect dan the influence,dan melalui berbagai database. (mis. Google Scholar, Emerald, Scopus). A total 7 articles were selected to be studied in literature review. From these studies we have managed to categories the influences of brand on hospital performance and patient behavioral expectation and reported on three categories, including the influences of brand on hospital performance, on patient behavioral expectation, and medical team in referral. From these studies we have managed to categorize even practical considerations that is considered as influence of brand on hospital performance and patient behavioral expectation are influence of brand on hospital performance, influence of brand on patient behavioral expectation, Medical team in referral. Increasing number of Hospital in Asia at the present triggers hospital to build a marketing strategy. Hospital branding is one of the choosen way for marketing which giving benefits for internal and externals. This study aims to identify the influences of brand on hospital performance and patient behavioral expectations. The research method is literature review with 7 included studies. Research related to branding in the field of healthcare services was searched using valid keywords, including hospital branding, hospital, patient combined with keywords such as the effect dan the influence,dan melalui berbagai database. (mis. Google Scholar, Emerald, Scopus). A total 7 articles were selected to be studied in literature review. From these studies we have managed to categories the influences of brand on hospital performance and patient behavioral expectation and reported on three categories, including the influences of brand on hospital performance, on patient behavioral expectation, and medical team in referral. From these studies we have managed to categorize even practical considerations that is considered as influence of brand on hospital performance and patient behavioral expectation are influence of brand on hospital performance, influence of brand on patient behavioral expectation, Medical team in referral.